Investigating the Effectiveness of Formative Homework Feedback - Hoepner, Jerry K.; Hemmerich, Abby L.; Elledge, Deborah; Doyle, Jordan; Wolosek, Ashley (My University, 2018)
The purpose of this current study was to evaluate the effectiveness of instructor feedback on quantity and quality of student preparatory assignments. Student researchers gathered quantitative data in the form of word count and qualitative data in the form of an anonymous survey.
Color poster with text, bar graphs, charts, and images.
Keywords: Posters; Homework; Feedback